Pendidikan Cinta Rasulallah SAW Studi Atas Makna, Tujuan dan Hikmah - Supriyatin (STIT Sirojul Falah Bogor, 2024)
It is love that motivates someone to do something to achieve their dreams. Feelings of love must be translated into real actions as the fruit of faith in the heart. Allah is the one who planted it, but Rasulullah saw it. who look after and care for him so that love grows and develops. All of us, Alhamdulillah, have heard and understood a lot about the birth of Rasulullah SAW, his holy sir, his noble character and his great state, where Allah swt destined him to be the opener of the door of intimacy for everyone and the key to wushul (achievement) for experts in perfection, so that no servant who can enter into the presence of Allah SWT. except by the way. And no one achieves His virtue, grace and perfection except through the Messenger of Allah. Not only that, Allah S.W.T. does not allow the servant to reach and approach Him except in the manner indicated by His beloved, Rasulullah SAW. This study examines how a person achieves love for Rasulullah SAW by understanding the meaning, purpose and wisdom of Rasulullah's love.